Жизнь , по слухам, одна !: роман / Т. Устинова - Устинова Татьяна (Первая среди лучших, 2010)
Экземпляры: ф.4 (20171129) / Инвентарный номер: 54539 / Цена: 30.00 / Авт.знак: У79 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6